2013
DOI: 10.1149/05701.1507ecst
|View full text |Cite
|
Sign up to set email alerts
|

Doped Samarium Ferrite Perovskites as Carbon and Sulfur Resistant Anodes for Low Temperature Solid Oxide Fuel Cells

Abstract: Perovskite type oxides (ABO3) have opened a new door to solve operational issues of SOFC anodes. One of the great advantages of these materials is that their properties can be easily tailored according to the desired applications, by introducing substitutions at A and B- sites. Doping Ce, Co and Ni in SmFeO3 solves not only the reduction instability issue of these perovskites, but also makes these materials suitable as anodes. The resistance to coke formation is shown for three prime candidates of this perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Because the samarium and iron concentrations are roughly equal in the (Sm, Fe)-rich zones, the most likely product of the iron diffusion into SDC is the SmFeO 3 perovskite (tolerance factor = 0.92). Samarium ferrites are primarily oxygen-ion conductors tested as gas sensors and SOFC anodes, with much lower p-type electronic conductivity. , This hypothesis is corroborated by the analysis of the microXANES spectra of iron in the LSCF and SDC regions of LSCF–SDC_72 h (see Figure ): the near-edge features are roughly the same in the various points investigated, indicating that iron keeps its coordination environment (perovskite B-site). Upon further inspection, however, interesting correlations can be drawn between edge features and distance from the interface.…”
Section: Resultsmentioning
confidence: 69%
“…Because the samarium and iron concentrations are roughly equal in the (Sm, Fe)-rich zones, the most likely product of the iron diffusion into SDC is the SmFeO 3 perovskite (tolerance factor = 0.92). Samarium ferrites are primarily oxygen-ion conductors tested as gas sensors and SOFC anodes, with much lower p-type electronic conductivity. , This hypothesis is corroborated by the analysis of the microXANES spectra of iron in the LSCF and SDC regions of LSCF–SDC_72 h (see Figure ): the near-edge features are roughly the same in the various points investigated, indicating that iron keeps its coordination environment (perovskite B-site). Upon further inspection, however, interesting correlations can be drawn between edge features and distance from the interface.…”
Section: Resultsmentioning
confidence: 69%
“…However, other perovskites have been reported to show an enhancement in the rate of hydrogen oxidation in the presence of H 2 S, including La 0.7 Sr 0.3 VO 3 (LSV) (11), Sm 0.95 Ce 0.05 Fe 0.97 Ni 0.03 O 3-δ (SCFN) (12), and Y 0.9 Sr 0.1 Cr 0.9 Fe 0.1 O 3-δ (YSCF) (13). For LSV, the observed enhancement was attributed to the formation of an active SrS phase, replacing an insulating phase (Sr 3 V 2 O 8 ) (11), while for SCFN and YSCF, it was suggested that the active phase that forms in the presence of H 2 S is probably FeS (12,13 (10,14,15), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For LSV, the observed enhancement was attributed to the formation of an active SrS phase, replacing an insulating phase (Sr 3 V 2 O 8 ) (11), while for SCFN and YSCF, it was suggested that the active phase that forms in the presence of H 2 S is probably FeS (12,13 (10,14,15), respectively. These La 0.3 M 0.7 Fe 0.7 Cr 0.3 O 3-δ (M = Sr, Ca) perovskite oxides have been successfully employed as both fuel and O 2 electrodes for SOFC/SOEC applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on its p-type semiconducting properties, this family is also promising gas sensor for detecting many volatile organic compounds, especially ethanol, benzene, xylene and so on [3]. They are also of fundamental interest for potential applications in catalysts [4], solid oxide fuel cells [5], and magneto-optic devices [6]. Among the family of ReFeO 3 , SmFeO 3 has been shown to have excellent device characteristics such as the fast magnetic switching [7] and the rotation of direction of the easy axis of magnetization from c axis to a axis at a quite high temperature (spin-reorientation transition, T SR = 480 K) [8].…”
Section: Introductionmentioning
confidence: 99%